Cerebral Salt-Wasting Syndrome in a Patient with Subacute Sclerosing Panencephalitis: The Use of Fludrocortisone in Treatment - Orkun Tolunay; Tamer Çelik; Aysu İlhan Yalaki; Duygu Artar; Ümit Çelik (Galenos Yayinevi, 2019)
Cerebral salt wasting syndrome (CSWS) is characterized by natriuresis and associated with hypovolemia, and hyponatremia. The underlying pathogenesis is not clearly known. It is often confused with syndrome of inappropriate anti-diuretic hormone release. Volume repletion and sodium replenishment and correction of the underlying cause are the most important components of treatment. As the awareness of CSWS, which is frequently described in neurosurgical patient, increases, the number of patients diagnosed increases and new factors are gradually defined in the etiology. In this study, we present a 16-year-old male patient, who was followed with the diagnosis of subacute sclerosing panencephalitis and developed CSWS and did not recover from hyponatremia despite sodium replenishment, and was successfully treated with fludrocortisone.